2013
DOI: 10.1152/ajpgi.00495.2012
|View full text |Cite
|
Sign up to set email alerts
|

Induction of COX-2 expression by Helicobacter pylori is mediated by activation of epidermal growth factor receptor in gastric epithelial cells

Abstract: DB. Induction of COX-2 expression by Helicobacter pylori is mediated by activation of epidermal growth factor receptor in gastric epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
(32 reference statements)
3
26
0
Order By: Relevance
“…12,17 C57BL/6 wild-type (WT) and Egfr wa5 mice possessing an antimorphic EGFR allele that attenuates EGFR phosphorylation, 18 were infected with PMSS1 for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…12,17 C57BL/6 wild-type (WT) and Egfr wa5 mice possessing an antimorphic EGFR allele that attenuates EGFR phosphorylation, 18 were infected with PMSS1 for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…A further effect of epithelial contact with the cagPAI type IV secretion system is higher expression of the EGFR and its activation leading to downstream activation of COX2 [197,198]. This is accompanied by a shift towards a proapoptotic homeostasis with increased expression of bax and decreased expression of bcl2 [199,200].…”
Section: Response To H Pylori In the Gastric Mucosamentioning
confidence: 99%
“…Consistently, the present study demonstrated that expression of 15-PGDH mRNA and protein was significantly suppressed in gastric cancer samples compared with control samples, and infection with H. pylori resulted in additional downregulation of 15-PGDH mRNA and protein levels. These findings indicated that H. pylori infection may trigger carcinogenesis of stomach cancer by elevating PGE 2 levels through modulating expression of Previous studies have also demonstrated that gastric tumors may be induced by activated macrophages in transgenic mice overexpressing COX-2 and the PGE 2 -converting enzyme microsomal prostaglandin E synthesis (25), and that COX-2 was induced by H. pylori infection (26,27). A significant upregulation of COX-2 was also previously identified in >70% of gastric cancer specimens, and this was reversed when H. pylori was eliminated (28).…”
Section: Discussionmentioning
confidence: 74%